Improving Diagnostic and Treatment Methods for Congenital Hydronephrosis in Children - Abdutolipov Abdullajon (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Congenital hydronephrosis is one of the most common congenital anomalies of the urinary system in children. The disease is characterized by dilation of the renal pelvis and calyces caused by impaired urine outflow. Recent advances in prenatal diagnostic methods have made it possible to detect the condition during pregnancy. Early diagnosis and timely treatment play a crucial role in preserving renal function and preventing complications. This article analyzes the etiology, pathogenesis, modern diagnostic approaches, treatment principles, and future prospects for improving the management of congenital hydronephrosis in children.